The incidence of isolated single umbilical artery in twins and adverse pregnancy outcomes. (27th January 2013) - Stout, Molly J.; Odibo, Anthony O.; Longman, Ryan; Shanks, Anthony L.; Cahill, Alison G.
ABSTRACT Objectives The aim of this study was to estimate the incidence of single umbilical artery (SUA) in twin pregnancies and to investigate whether SUA in twin gestations is associated with adverse obstetric outcomes. Methods We performed a retrospective cohort study of consecutive twin pregnancies over 17 years at a tertiary care hospital. Primary exposure was SUA in one or both twins documented at routine second trimester anatomic survey. Adverse obstetric outcomes included small for gestational age (SGA), placental abruption, and preterm birth, evaluated in univariable and multivariable analyses. Analysis was performed both at the pregnancy level and at the fetal level using paired analyses to account for the non‐independence of twin pairs. Results Of the 2378 twin pregnancies without major anatomic abnormalities, 1.7% (n = 40) had SUA. Only one pregnancy (one monochorionic twin pair) was complicated by both twins having SUA. Twin fetuses with SUA are at increased risk for SGA (aOR = 2.1 (1.2–4.1), p = 0.03) after adjusting for pertinent confounding factors, similar to the findings of previous studies in singleton pregnancies. In addition, twins with SUA may be at increased risk for preterm delivery before 28 weeks compared with twin pregnancies with normal three‐vessel umbilical cords (adjusted odds ratio (aOR) 3.2 (1.3–7.89.4), p = 0.01). Conclusions The incidence of SUA in twin gestations in this cohort is significantly less than the recently published data. Similar to reports in singleton gestations, SUA appears to be associated with an increased risk for SGA in twins. © 2013 John Wiley & Sons, Ltd.